PELAKSANAAN PENETAPAN STATUS PENGGUNAAN TERHADAP BARANG RAMPASAN NEGARA DI KEJAKSAAN NEGERI SURAKARTA - Nuraini, Isna; Kristiyadi, Kristiyadi (Sebelas Maret University, 2021)
This article aims to find out how the Implementation of Determination of Use Status at the surakarta District Attorney's Office in Decision Number 191/Pid.B/2000/PN.Ska is based on applicable laws and regulations. The method used in this research is normative legal research which is prescriptive and applied. Sources of legal research consist of primary legal materials and secondary legal materials. Based on this research, it was found that the implementation of the Determination of Use Status at the Surakarta District Attorney was carried out with the stages of application by the Surakarta District Attorney, research by the Minister of Finance, and a decision to determine the status of use by the Minister of Finance and the High Court. This is in accordance with Law Number 1 of 2004 concerning the State Treasury, Government Regulation Number 28 of 2020 concerning Management of State/Regional Property, PMK No. 145/PMK.06/2021 concerning Management of State Property Derived from State Confiscated Goods and Goods of Gratification and Prosecutor's Regulation No. 7 of 2020 concerning Guidelines for Asset Recovery.Keywords: Determination of Use Status, Evidence, Attorney